Contextual Learning: Implementation and Challenges for Science Teacher in Private Middle School - Situmorang, Risya Pramana; Suwi, Elia; Nugroho, Failasuf Aulia (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This purpose of this study is to: (1) describe the implementation of contextual learning by science teacher in Salatiga Private Middle School, (2) analyze the challenges of science teacher in Salatiga Private Middle School in implementing contextual learning. The study employed qualitative research in which the sample was 4 teachers of private middle school of Salatiga. The data obtained from the observation and questionnaire instruments constructed from six criteria. The criteria of contextual learning are: 1) constructivism, 2) asking, 3) finding, 4) learning community, 5) modeling, 6) reflection. Data analysis from the research that has been conducted is by processing data descriptively. The research shows that the implementation of contextual learning in every Private Middle School of Salatiga for science subject are on the good category (score interval: 2,82 ≤ score < 3,37). The highest accomplishment from the whole indicator of contextual learning from finding aspect with score 3,00 (good category). Teacher's challenges in implementing contextual learning, in general, are the limited facility to apply scientific method through practicum or experimenting in the laboratory, lack of opportunities for teachers in developing contextual-based media, and lack of assistance provided by the teacher in the aspects of a learning community, constructivism, and finding.